Will-to-Win, Self-Esteem, and Dispositional Flow State among adolescent athletes in India - A path analysis and comparisons by gender and level of achievement - Ahmed, M. D.; Ho, W. K. Y.; van Niekerk, R. L.; Begum, S. (African Journal for Physical Activity and Health Sciences, 2020)
This study aimed to examine the relationships between athletes` will-to-win, their self-esteem, and dispositional flow state by presenting a structural model of the relationships. Further, gender and competitive level group differences among adolescent athletes in India were explored. A purposive sample of 318 adolescent athletes (male: n = 188; female: n = 130) with a mean age of 16.10 ± 1.01 years, who participanted in basketball, football and volleyball competitions, completed the Rosenberg Self-Esteem Questionnaire, Will-to-Win Questionnaire and the Dispositional Flow Scale-2. Significant differences were found between the two competitive levels and gender groups. Players participating on Inter-state level had significantly higher self-esteem, will-to-win and dispositional flow (such as challenge skill balance, clear goals and concentration on the task at hand) than participants at Inter-district level. Male athletes had significantly higher self-esteem (p=.077) and dispositional flow (such as action awareness merging; p=.004), concentration, loss of self-consciousness (p=.050) and transformation of time (p=.001) than female athletes. A significant positive relationship was found between self-esteem, will-to-win and the dispositional flow subscales. Lastly, the CFA (path analysis) showed excellent model fit between Will-to-Win -> Self-Esteem -> Dispositional Flow. Athletes participating on higher competitive levels reported superior mean scores in five factors such as self-esteem (31.14 ± 6.77), will-to-win (10.24 ± 2.32), challenge skill balance (17.34 ± 2.17), action awareness merging (15.25 ± 2.99) and clear goals (16.48 ± 2.50). Male athletes had higher mean scores on self-esteem and dispositional flow state than female athletes. However, will-to-win did not show any significant gender difference. Additionally, the linear structural model of the relationship between will-to-win mediating selfesteem with dispositional flow provided excellent model fit.